RELIGIUSITAS, HARGA DIRI DAN PERILAKU SEKSUAL PRANIKAH REMAJA - Anis Rosidah (University of Merdeka Malang, 2012)
Abstract The objective of this study is to know the correlation between self esteem and religiousity in adolescent premarital sexual behavior. Self-esteem is an individual assessment of herself in a positive or negative. Meanwhile, religiosity is the internalization of religious values ??in a person. While premarital sexual behavior is behavior that is driven by sexual desire to the opposite sex or same-sex marriages performed outside. The research was conducted on students of SMAN 1 Grogol Kediri teens aged 15-18 years who were or had been dating and not married by the number of subjects as many as 131 students, which consisted of 19 male students and 112 female students. Data collection tool in the form of premarital sexual behavior scale consists of 48 aitems, self-esteem scale consists of 37 aitems, and religiosity scale consisting of 41 aitems. Data analysis was done by using multiple linear regression analysis with the help of a statistical program SPSS 16.0 for Windows. From the analysis of data obtained by the correlation between self-esteem with premarital sexual behavior of -0,269 with a significance of 0.001. This means that there is a very significant negative relationship between self-esteem and adolescent premarital sexual behavior. Meanwhile, the value of the correlation between religiosity with premarital sexual behavior of -0,471 with a significance of 0.000. This also means that there is a very significant negative relationship between religiosity with adolescent premarital sexual behavior. In the F test F calculated values ??obtained 21,915 F table 4,771 with the value p 0.000 0.01. This suggests that self-esteem and religiosity can be used to measure adolescent premarital sexual behavior. The results of data analysis also showed the value of R Square (R2) is 0.255. This means that in this study self-esteem and religiosity contributed by 25.5% against premarital sexual behavior with the contribution of each variable at 4.97% for the variable self-esteem and 20.53% for the variable of religiosity. Key words: self-esteem, religiousity, premarital sexual behavior, adolescents